BATASAN HAK SUAMI DALAM MEMPERLAKUKAN ISTRI SAAT NUSYUZ - Risalan Basri Harahap (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
Nusyuz is a conception of classical law of the past, what we inherit not only as part of the Islamic thought tradition has even been codified as a standard rule of law. This is reflected in the existence of several rights of the husband in cracking down on the wife who is oblivious without clear boundaries. Whereas for the wife almost has no room to defend themselves and their rights before the law in a balanced manner. Therefore, in this study as well as legal research in general, the approach used is doctrinal research in order to find the principle or doctrine of positive law that applies in relation to the problem under study, in the form of opinions and ideas from legal experts regarding boundaries. the limitation of the husband's right to treat his wife who is infamous. Then describe it in general, classify it and analyze it critically using inductive reasoning. This is because in every discussion of the issue of nusyuznya the wife often forgets the basic principle or principle as a parameter in granting restrictions on the rights and authority of the husband over the wife. Like the principle of the pattern of relations between husband and wife in Islam, the purpose of sanctions and also in seeing the legal substance of the actions of Nusyuz itself, both in terms of quality, quantity and things that trigger the problem. Nusyuz's legal issues often have a negative impact on the position of women, and can even be one of the triggers of violence against them.